Regulation of synaptosomal 2-arachidonoylglyceol hydrolysis by Cannabis extracts during aging - Salas, Sabrina Rosicler (2021)
The availability of the main neuroprotective endocannabinoid, 2-ara- chidonoylglycerol (2-AG), was found to decrease in rat cerebral cor- tex (CC) synaptosomes (syn) during aging. It was also demonstrat- ed that 2-AG metabolism can be modulated by its own receptors. Moreover, phytocannabinoids (PC) present in Cannabis extracts (CE), have been proposed as neuroprotective agents and are be- ing used in several studies to treat neurodegenerative processes. The aim of this study was to evaluate if THC present in CE could modulate 2-AG hydrolysis by monoacylglycerol lipase (MAGL). To this end, delta-9-tetrahydrolcannabinol (THC) enriched CE were ob- tained from Cannabis Y Griega female flowers, previously grinded and heated 115°C for 40 min. Extractions were performed by add- ing 5% (w/v) ethanol, vortexed, sonicated and agitated. The mixture was centrifuged and the supernatant was evaporated under stream of N2 . THC, cannabidiol (CBD) and cannabinol (CBN) were quan- tified by HPLC. CC syn from adult (4-6 months) and aged (24-26 months) rats were isolated by differential centrifugation and purified in ficoll gradients. MAGL activity was assessed by incubating syn with either THC enriched CE (10-3-50 μM THC) or 1 μM pure THC, and [3 H]-MAG, simultaneously. It was observed that CE containing 1 μM THC decreased MAGL activity in aged (p=0.0166) but not in adult syn (p>0.05). However, 1 μM pure THC failed to modulate 2-AG hydrolysis (p>0.05). This findings, could suggest that THC enriched CE could attenuate the deregulation of 2-AG metabolism observed in aging, and that this effect could only be generated when syn are exposed to the PC in the presence of the entire CE.